2012
DOI: 10.1254/jphs.11r03fm
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Strategy for Amino Acid Medicine: Prophylactic and Healing Promoting Effect of Monosodium Glutamate Against NSAID-Induced Enteropathy

Abstract: Abstract.We reviewed the effect of monosodium glutamate (MSG) on the development and healing of nonsteroidal anti-inflammatory drug (NSAID)-induced small intestinal lesions in rats. Loxoprofen (60 mg/kg, p.o.) induced lesions in the small intestine within 24 h, accompanied by a decrease of Muc2 expression and an increase in enterobacterial invasion and inducible nitric oxide synthase (iNOS) expression. These lesions were prevented when MSG was given as a mixture of powdered food for 5 days before the loxoprofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Feeding of L-Glu (1 or 5 %) for 5 days prior to one time NSAID treatment significantly reduced intestinal lesions while daily treatment for 5 days with L-Glu after NSAID treatment accelerated ulcer healing [50], consistent with our finding that luminal amino acids prevent the formation and promote healing of NSAID-induced enteropathy, although one dose of L-Glu/IMP did not significantly inhibit ulcer formation in our study. The combination of metformin, which increases the release of GLP-1 and 2, with a DPPIV inhibitor, prevents 5-fluorouracil-induced mucositis [51].…”
Section: Discussionsupporting
confidence: 90%
“…Feeding of L-Glu (1 or 5 %) for 5 days prior to one time NSAID treatment significantly reduced intestinal lesions while daily treatment for 5 days with L-Glu after NSAID treatment accelerated ulcer healing [50], consistent with our finding that luminal amino acids prevent the formation and promote healing of NSAID-induced enteropathy, although one dose of L-Glu/IMP did not significantly inhibit ulcer formation in our study. The combination of metformin, which increases the release of GLP-1 and 2, with a DPPIV inhibitor, prevents 5-fluorouracil-induced mucositis [51].…”
Section: Discussionsupporting
confidence: 90%
“…He clearly showed that glutamate-supplemented foods could protect non-steroid anti-in‰ammatory drug (NSAID)-induced gastric and duodenal ulcers in rat models. 54) The protective eŠects of glutamate were observed in H. pylori infected-gastric ulcers in the gerbil. 55) Oral care Saliva is essential for the maintenance of oral mucosa circumstances as well as oral functions such as speech, mastication, swallowing and taste sensation.…”
Section: Improvement In Enteral Nutritionmentioning
confidence: 99%
“…12 Glutamate, an amino acid whose metabolism is tightly related to glutamine metabolism in intestinal epithelial cells, 13 has been reported to promote small intestine MH after chemically induced enteropathy in rats. 14 Glutamate and glutamine are well known to be major fuels from the arterial origin for colonic epithelial cells. They are intensely oxidized by these cells 15,16 in a context of high energy requirement for the colonic epithelium renewal, thus requiring intense anabolic metabolism.…”
mentioning
confidence: 99%